2004
DOI: 10.1002/ijc.20387
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the orphan nuclear receptor RORα counteracts the proliferative effect of fatty acids on prostate cancer cells: Crucial role of 5‐lipoxygenase

Abstract: The incidence of prostate carcinoma is very low in Eastern countries, such as Japan, suggesting that life style conditions may play a crucial role in the development of this pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 44 publications
3
34
0
Order By: Relevance
“…Histological analysis of human adenoma samples found that 5-LOX expression was strongly correlated with polyp size and intra-epithelial neoplasia. Consistent with these findings the addition of 5-HETE to breast and prostate cancer cells in vitro enhanced proliferation (Avis et al, 2001;Moretti et al, 2004) and 5-LOX inhibition induced apoptosis in LNCaP and PC3 prostate cancer cells; thus, 5-LOX metabolites maintain tumor cell viability (Ghosh & Myers, 1998). Cell death was prevented by direct addition of 5-HETE and its analogues (Ghosh & Myers, 1998).…”
Section: Lox Metabolites In Tumorigenesissupporting
confidence: 77%
“…Histological analysis of human adenoma samples found that 5-LOX expression was strongly correlated with polyp size and intra-epithelial neoplasia. Consistent with these findings the addition of 5-HETE to breast and prostate cancer cells in vitro enhanced proliferation (Avis et al, 2001;Moretti et al, 2004) and 5-LOX inhibition induced apoptosis in LNCaP and PC3 prostate cancer cells; thus, 5-LOX metabolites maintain tumor cell viability (Ghosh & Myers, 1998). Cell death was prevented by direct addition of 5-HETE and its analogues (Ghosh & Myers, 1998).…”
Section: Lox Metabolites In Tumorigenesissupporting
confidence: 77%
“…These effects had been observed in tumor cell lines of breast (39), prostate (40) and colon carcinoma (41). Melanoma is an aggressive form of skin cancer associated with high mortality and limited response to therapy once extended beyond the skin (42)(43)(44).…”
Section: Introductionmentioning
confidence: 78%
“…Melatonin nuclear receptors, recently identified in keratinocytes, melanocytes and fibroblasts (18) as well as in hair follicles (28), belong to the retinoid orphan receptor subfamily (RZR/ROR). It was shown that all these human (18,40,59). Here, we tested melatonin for its potential oncostatic effects by assaying for proliferation and colony growth suppression in four different melanoma cell lines (three amelanotic lines including SBCE2, WM-98 and WM-164 derived from vertical and radial growth phases or metastasis, respectively, and SKMEL-188, which can produce melanin pigment).…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant AA metabolism in tumor cells seems to be dependent on the action of COX-2 and specific LOX (Cuendet & Pezzuto 2000), and these enzymes are over-expressed in PCa in a strict association with tumor grade (Madaan et al 2000). Although different LOXs may exert opposite effects on PCa cells, recent studies have focused on 5-LOX activity as a key regulator of tumor aggressiveness in PCa cell lines (Ghosh & Myers 1998a, Moretti et al 2004, Hassan & Carraway 2006. Moreover, 5-LOX has been considered an attractive target, together with COX-2, in antitumoral therapy, in cancer types possessing a basal high capacity in metabolizing AA, like PCa (Gugliucci et al 2002).…”
Section: Introductionmentioning
confidence: 99%